TECHNICAL CHALLENGES, IMPACTS AND PERSPECTIVES FOR ELECTRIC VEHICLES (EVS) - Lewandoski, Cristiano Fernando; Santos, Reginando Ferreira; Carniatto, Evelyn Tânica; Miranda , Amauri Ghellere Garcia; Sio, João Paulo Man Kit; Ikpehai, Augustine (International Journal of Environmental Resilience Research and Science, 2022)
Preventing environmental issues and growing concerns about global energy crises are driving the need for new opportunities and technologies that can meet significantly greater demand for cleaner generation and products, zero-carbon, and sustainable energy systems. This requires developing more efficient transport and energy generation. Changing the transport model to electric is a promising approach for ecological systems and for reducing the problems of climate change. This article inspects the current status, latest deployment, and challenging issues when installing an electric vehicle charging and infrastructure (EVs) system in conjunction with various international standards and charging codes. The article further analyzes the impacts of (EVs) and perspectives on society. A complete assessment of charging systems for (EVs) with battery charging techniques. Besides, the beneficial and harmful impacts of (EVs) are categorized and carefully reviewed. Corrective measures for harmful impacts are presented and the benefits obtained from them are highlighted. Bidirectional charging offers the vehicle’s key feature for smart grid technology. In this article, the current challenging issues due to the massive deployment of (EVs) and future research trends are also presented.